Partnerships for Active Children in Elementary Schools (PACES): First year process evaluation. (April 2018) - Egan, Cate A.; Webster, Collin; Weaver, R. Glenn; Brian, Ali; Stodden, David; Russ, Laura; Nesbitt, Danielle; Vazou, Spyridoula
Highlights: The community-based participatory research component yielded the largest increase in teacher's promotion of classroom physical activity. This study is the first to report systematic (valid, reliable) observation data of classroom teacher's promotion of physical activity. Teachers should be provided with ample contextually sensitive resources for promoting classroom physical activity. Abstract: Movement integration (MI) is a strategy within comprehensive school physical activity programs (CSPAP). School-university partnerships are recommended to leverage teachers' capacity to use MI. A mixed method process evaluation was conducted of the first year of implementing Partnerships for Active Children in Elementary Schools (PACES). Classroom teachers ( N  = 12) from four schools participated. Data were collected in Fall 2014 (baseline) and Spring 2015 (∼ four months of intervention) using the System for Observing Student Movement in Academic Routines and Transitions and semi-structured interviews. There were no significant differences between intervention classrooms and control classrooms MI promotion. Differences approaching significance ( U  = 5, p  = 0.04, d  = 1.2) were observed when comparing classrooms that received two (community of practice, community-based participatory research) or three components (two components plus service learning) of the intervention and classrooms that received one (community of practice) or no components. Qualitative findings revealed that teachers in classrooms that were more successful responded more favorably to the intervention components than teachers in classrooms that were less successful. Quantitative and qualitative results supported the effectiveness of community-based participatory research as a component of PACES. This study provides information about MI process variables in the context of a CSPAP intervention.